Policy of the President of the Republic of Kazakhstan N.A. Nazarbayev and mass media (Herald of Journalism, 2016)
In article the author analyzes the solution of problems, modern development and interrelation of the state and modern society in mass media through a prism of political activity of the President of the Republic of Kazakhstan N.A.Nazarbayev. In mass media the civic stand of the President of RK is presented. And also mutual cooperation of the head of state and mass media. The author considers the solution of problems of mass media, a course of board and illumination of views and statements of the President of the Republic of Kazakhstan in mass media.
Keywords: mass media